STRATEGIC INTEGRATION OF CHINA-PAKISTAN ECONOMIC CORRIDOR (CPEC) IN ENHANCING THE MARINE FISHERY SECTOR OF PAKISTAN: A PATHWAY TO SUSTAINABLE ECONOMIC GROWTH - SHAHZAD, SM; ALI, S; KHAN, MR; KHALID, MM (Biological and Clinical Sciences Research Journal, 2024)
The marine fishery sector in Pakistan is particularly important in terms of the country’s economy but is still unexplored with problems such as old equipment, limited cold storage and processing, and not much investment made. Due to the emphasis on connectivity and economic cooperation under the framework of the China-Pakistan Economic Corridor (CPEC), it is possible to provide a strategic impetus to the development of the fishery sector. This research work seeks to establish how CPEC may improve the marine fishery industry of Pakistan and find out how the sector may benefit from CPEC investments in infrastructure and related facilities. The specific research questions the way CPEC infrastructure and investment could be optimally used for the development of the marine fishery sector of Pakistan for possible economic gains that could be associated with the integration of CPEC into the fishery sector. The study adopts a descriptive research type of approach whereby the researcher relies on secondary sources of information and analyzed data to assess the status of the marine fishery of Pakistan, identify the opportunities under CPEC for the sector, and establish how the sector can effectively integrate into the framework. The importance is in bringing attention to an overlooked sector that may benefit from the efficient use of CPEC projects. With investment and cooperation in the agriculture and socio-economic sectors, integration in the fishery sector will enhance Pakistan’s blue economy and sustainable economic development.